Prediction of type 2 diabetes mellitus using fasting plasma glucose and HbA1c levels among individuals with impaired fasting plasma glucose: A cross-sectional study in Thailand - Tullaya Sitasuwan (2020)
© 2020 Author(s). Objectives About 11%-30% of individuals with impaired fasting plasma glucose (IFG) have type 2 diabetes mellitus (T2DM), diagnosed by the 75 g oral glucose tolerance test (75 g OGTT). This study investigated (1) the prevalence and cut-off levels for fasting plasma glucose (FPG) and glycated haemoglobin A1c (HbA1c) in IFG individuals that most effectively predict the presence of T2DM diagnosed by a 75 g OGTT; (2) the predictors associated with T2DM; and (3) the pathophysiological characteristics of patients with IFG. Materials and methods A single-centre, cross-sectional study was conducted in a primary care setting. A standard 75 g OGTT was performed on 123 subjects with IFG. Their beta-cell function and insulin resistance were calculated through plasma glucose and insulin levels monitored during the 75 g OGTT. Results In the IFG subjects, the prevalence of T2DM using the 2-hour postload plasma glucose (2hPG) criterion was 28.5%. Pre-diabetes and normal glucose metabolism were found in 48.7% and 22.8%, respectively, by 75 g OGTT. An HbA1c level ≥6.0% or FPG ≥5.9 mmol/L were the optimal cut-off thresholds for the prediction of the presence of T2DM. HbA1c had a sensitivity of 76.7% and specificity of 55.7% (95% CI 57.7% to 90.1% and 95% CI 43.3% to 67.6%, respectively), while FPG had a sensitivity of 85.7% and specificity of 23.9% (95% CI 69.7% to 95.2% and 95% CI 15.4% to 34.1%, respectively). The presence of metabolic syndrome, a higher HbA1c and higher FPG levels were associated with the risk of T2DM in the Thai IFG population. Conclusions Almost one-third of the people with IFG had T2DM diagnosed by the 2hPG criterion. HbA1c was more effective than FPG in predicting the presence of T2DM in the IFG subjects. IFG individuals with HbA1c≥6.0% or FPG≥5.9 mmol/L should be advised to undergo a 75 g OGTT to detect T2DM earlier than otherwise.